Semantic-Pragmatic Impairment in the Narratives of Children With Autism Spectrum Disorders - Kenan, Naama; Zachor, Ditza A.; Watson, Linda R.; Ben-Itzchak, Esther (Frontiers in Psychology, 2019)
Narrative impairments are common in autism spectrum disorders (ASD). The Autism Diagnostic Observation Schedule (ADOS) battery includes a story-telling activity using a picture book called Tuesday. The current study aimed to identify differences between children with ASD and children with typical development (TD) on the production of Tuesday narratives, with a special focus on semantic-pragmatic aspects. Participants were 48 cognitively-able boys, in the age range of 4;10-7;0 years. Twenty-four participants were boys with ASD and 24 participants were TD boys. The semantic-pragmatic analysis included measures of: story details (characters setting, objects, and actions), central ideas, evaluative comments, and unrelated text. Results showed that the narratives produced by children with ASD included fewer central ideas, and fewer settings, characters, and actions, but not objects, as compared with the narratives produced by their TD peers. The number of evaluative comments and utterances that were unrelated to the story did not differ between the groups. A negative correlation was found between the autism severity level and the number of central ideas and number of characters mentioned in the narratives of the ASD participants. Taken together, these findings point to a semantic-pragmatic impairment in ASD. Some of the results can be explained by cognitive deficits in maintaining central coherence (the Weak Central Coherence account). This study has important clinical implications. Defining the specific differentiating measures can maximize the use of the ADOS story-telling activity by clinicians. The association found between the autism severity level and some of the semantic measures can be used in evaluating the severity of the ASD symptoms